2014
DOI: 10.1061/(asce)gt.1943-5606.0001061
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge Modeling of Soil-Structure Interaction in Energy Foundations

Abstract: This study presents a centrifuge modeling approach to characterize the transient thermo-mechanical response of energy foundations during heating-cooling cycles in order to provide data for calibration and validation of soil-structure interaction models. This study focuses on the response of a scale-model energy foundation installed in an unsaturated silt layer with end-bearing boundary conditions. The foundation response was assessed using embedded strain gages and thermocouples. Other variables monitored incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(75 citation statements)
references
References 18 publications
1
71
2
1
Order By: Relevance
“…The fullscale field experiments reported by Brandl (2006), Laloui et al (2006), Bourne-Webb et al (2009), Akrouch et al (2014), Mimouni and Laloui (2015), Murphy et al (2014) and Wang et al (2015), as well as experimental set-ups by McCartney and Rosenberg (2011), Kalantidou et al (2012), Stewart and McCartney (2013), Ng et al (2014) and Yavari et al (2014a) have provided an invaluable insight into the behaviour of thermo-active piles. Moreover, the results of the first field tests (Bourne-Webb et al, 2009;Brandl, 2006;Laloui et al, 2006) have led to the development of a simplified descriptive framework for thermo-mechanical pile response (Amatya et al, 2012;Bourne-Webb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The fullscale field experiments reported by Brandl (2006), Laloui et al (2006), Bourne-Webb et al (2009), Akrouch et al (2014), Mimouni and Laloui (2015), Murphy et al (2014) and Wang et al (2015), as well as experimental set-ups by McCartney and Rosenberg (2011), Kalantidou et al (2012), Stewart and McCartney (2013), Ng et al (2014) and Yavari et al (2014a) have provided an invaluable insight into the behaviour of thermo-active piles. Moreover, the results of the first field tests (Bourne-Webb et al, 2009;Brandl, 2006;Laloui et al, 2006) have led to the development of a simplified descriptive framework for thermo-mechanical pile response (Amatya et al, 2012;Bourne-Webb et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is possible owing to scaling laws derived by Savvidou (1988), who determined the time scaling factor of N 2 (N being the applied enhanced gravity in the centrifuge) for heat flow in accelerated gravity experiments, which enables multi thermal cycles to be simulated in a shorter duration (hours) that would normally take years at full field scale. Notable centrifuge investigations benefiting from this scaling relationship include Stewart and McCartney (2014), Ng et al (2014), Britto et al (1989), Goode et al (2014), and Stewart and McCartney (2012). These studies considered a range of various soil types with reported observations of increased pile settlements and ratcheting over several thermal cycles.…”
Section: Energy Geotechnicsmentioning
confidence: 99%
“…Typically, laboratory THM soil characterisation is carried out by adapting standard laboratory soil testing devices to non-isothermal conditions, mainly oedometer, direct/simple shear, and triaxial devices, and more recently by means of centrifuge modelling [213]. The temperature controlled triaxial test is one of the best-established approaches for characterising THM behavior due to its relative simplicity and capability to control key variables.…”
Section: Laboratory Thm Characterisationmentioning
confidence: 99%